Combination Olanzapine and Samidorphan for the Management of Schizophrenia and Bipolar 1 Disorder in Adults: A Narrative Review - Hannah W. Haddad; Elena Boardman; Brooke Williams; Rama Mouhaffel; Adam M. Kaye; Alan D. Kaye (Health Psychology Research)
Schizophrenia is a debilitating psychotic disorder characterized by positive symptoms such as delusions, hallucinations, and disorganized thoughts, and negative symptoms like lack of effect or motivation. Bipolar 1 disorder (B1D) is a psychiatric illness characterized by recurrent manic episodes in alternation with depressive episodes and interspersed periods of euthymia, ultimately resulting in psychological distress and impairment of daily functioning. Effective treatments are needed for both schizophrenia and B1D to reach the treatment goals of reducing the debilitating symptomology, improving social functioning and quality of life, and increasing the chances of recovery and more favorable long-term outcomes. To date, olanzapine is one of the most efficacious atypical antipsychotics (AAPs) for the treatment of both schizophrenia and B1D and is associated with fewer extrapyramidal effects compared to other treatments. However, compared to other AAPs, olanzapine is associated with a greater chance of metabolic syndrome, limiting its clinical use and affecting treatment compliance. Samidorphan mitigates the weight gain side effects of olanzapine by antagonizing μ-, κ-, and δ-opioid receptors. The use of combination drugs to treat psychiatric conditions is an emerging field with the goal of increasing therapeutic efficacy and decreasing undesirable side effects. Clinical trials have demonstrated combination on olanzapine and samidorphan (OLZ/SAM) treatment resulted in significantly less weight gain than olanzapine monotherapy. Clinical trial patients reported improvements in symptoms of psychosis, reduced weight gain, and overall satisfaction with their treatment. OLZ/SAM has been as shown to be a safe and effective pharmaceutical option for the clinical management of schizophrenia and B1D.